The Relation of metacognition of students in physical education with social and cultural environment - Chatzipanteli Αθανασία; Diggelidis Νικόλαος; Kurgiridis Παύλος (Inquiries in Physical Education and Sport, 2012)
The aim of the study was to investigate students’ metacognition from different social environment in physical education classes. One hundread and two students (45 boys and 57 girls) eleven years old, participated in this study. Forty three students were from the urban area, thirty nine from the semi-urban area and twenty from the rural village. Two variables were studied: a) place of residence and b) parental education. Metacognitive Process in Physical Education Questionnaire (Theodosiou & Papaioannou, 2006) was used in order to assess metacognitive activities. Statistical analysis showed that the urban students of educated parents had better scores in metacognition than the students of less educated parents from the semi-urban and rural areas. The findings revealed that the place of residence and the parental education can influence students’ metacognition.